(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Handicrafts are among the most important and valuable works in the social life of the afghan people. since ancient times, the people of Afghanistan did not have access to advanced production devices, they had to prepare their needs, which are the most urgent needs of a society. This motivation caused the productin work to be done by hand, which became known as handicrafts. These industries, which include household items such as: carpets, rugs, felt, cribe, doors, chairs, kitchen utensils, ornaments, etc…constitue the handicrafts of the people of Afghanistan and currently modern items are available. people are supposed to be able to use it easily, but still afghan handicrafts have not lost their special value and status.